Teaching resources in Philippine nationalism for secondary social studies teachers - Sapundan, Filipinas Santos 1940- (1986)
The purpose of this study was to prepare teaching materials for teachers of Social Studies in teaching Philippine Nationalism as a subject in the secondary school. This study also aimed to develop a syllabus for the teaching of Philippine Nationalism as an elective subject in the fourth year secondary level. This syllabus can be used by Social Studies teachers as a teaching resource in the teaching of Philippine Nationalism. The study also aimed to prepare some readings for specific topics that will be readily at hand for the Social Science teachers who are teaching Philippine Nationalism. This readings will be useful for those teachers whose background knowledge about history, anthropology, political science, and other Social Science discipline is limited.
Vita.
Thesis (M.A.T. Social Studies)--University of the Philippines, Diliman.
Keywords: Nationalism -- Study and teaching (Secondary) -- Philippines; Social science teachers -- Philippines